SPIRITUAL ENTREPRENEURSHIP DALAM PEMBERDAYAAN EKONOMI UMAT (Studi terhadap Tarekat Idrisiyah Pageningan Tasikmalaya) - Dede Aji Mardani (Universitas Siliwangi, 2019)
This study aims to determine the pattern of intermediate application doctrine, workship or rite (dhikr) vertically and alms horizontally and their impact on empowerment community economy in a sustainable way at once to improve the quality of life of people who are decent, self-ufficient primary sector competition for people's lives. Which method used in this research is qualitative approach phenomenology. The researcher jumped directly into the field and interviewed the object of his research. The results of this study indicate that the level of leadership spirituality, doctrine and dzikir tarekat followers have an impact on acceptance and utilization and get sympathy from the community local Muslims which can influence branding, income, entrepreneurship and encourage charismatic traits for this tarekat.